Editorial: Italy's "Charter of Workers' Rights" turns fifty - Carlo D'Ippoliti (PSL Quarterly Review, 2021)
This short editorial introduces the contributions to a special issue celebrating the fiftieth anniversary of the Italian Statuto dei lavoratori (Charter of Workers' Rights). Such anniversary both reaffirms how crucial workers' movements have been for the design and implementation of progressive policies in Europe, and-by contrast-highlights current difficulties.
Keywords: J08; J28; J53; 330; Charter of Workers' Rights